Komoditas Unggulan Potensial Jenis Empon-Empon Untuk Meningkatkan Produktivitas Hutan Rakyat Di Ciamis Jawa Barat - Suhartono Suhartono (ULIN: Jurnal Hutan Tropis, 2021)
Private forest farming has been a new source of family income for farmers in the Ciamis District. However, it has not been could to fully support the living needs of farmer families. Therefore, a strategy is needed to increase the productivity of private forest lands wich can meet the short-term and long-term needs of farmers. This study aims to identify the superior commodity types of empon-empon wich has the potential to increase the productivity of community forest lands. The study desk method was used in this research by utilizing statistical data on the production of biopharma plants in Ciamis Regency and West Java Province. To find out the superior commodities, a Location Quotient analysis approach was used. There were six types of empon-empon that have been cultivated in Ciamis Regency, including Zingiber officinale, Amomum compactum, Kaepferia galanga, Curcuma longa, Alpinia galanga, and Curcuma zanthorrhiza. Amomum compactum types is considered as a potential commodity to be developed on private forest land because it has a comparative advantage with LQ value>1.